PARAMETRIC ANALYSIS OF LONGITUDINAL STABILITY UNMANNED AERIAL VEHICLE - Udartsev, Ievgen; Bondar, Alexandr; Plakhotniuk, Ievgen (Proceedings of National Aviation University (archive), 2013)
<!--[if gte mso 9]> 1024x768 <![endif]-->We consider the aerodynamic characteristics of unmanned aircraft container type, which were obtained in a wind tunnel and refined amended by soot blowing elements propeller system and the influence of the earth's surface. The estimation of longitudinal static stability and its dependence on altitude, damping, coordinates of center of gravity, shoulder horizontal tail, wings rejection of mechanization. The variation of these parameters enables to optimize balancing system with minimal losses.<!--[if gte mso 9]> Normal 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Обычная таблица"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->